FACULTY DEVELOPMENT IN MEDICAL INSTITUTIONS: WHERE DO WE STAND IN PAKISTAN? - Mukhtar, Fatima; Chaudhry, Abdul Majeed (Journal of Ayub Medical College Abbottabad, 2010)
Background: The term ’˜Faculty Development’ encompasses all those activities which help faculty members enhance their academic competencies. It comprises three domains: personal development, professional development, and instructional and course development. The objectives of this study were to determine the proportion of medical colleges involved in faculty development activities, to assess the types of faculty development activities, and to identify the factors influencing such activities, along with formulating recommendations for faculty development. Methods: A cross-sectional study was conducted in the medical colleges (public and private) of Pakistan from September to December 2010. A questionnaire was designed through literature review, was pre-tested and then sent via mail to principals of the institutions outside Lahore. Questionnaires were self-administered to respondents within Lahore. Apart from describing the data, Chi-square and Fisher’s exact tests were applied to determine statistical association between categorical variables at p‰¤0.05. Results: All the 65 public and private sector medical colleges recognised by the Pakistan Medical and Dental Council (PMDC) at that time were included in the study. Responses were received from 45 medical institutions, of which 37 (82%) were involved in faculty development activities. Training on communication skills were provided by 31 (84%), and teaching skills by 30 (81%) institutes. Stress management was the topic addressed by 15 (40%) institutes. Most institutes conducted such activities once a month (43%), followed by once every six months (30%). Faculty at all levels was equally involved in training activities, except senior registrars involved by 5 (14%). The presence of Medical Education Department (DME) in the college (p<0.01), the respondent’s designation (p=0.0038) and the provincial location of the college (p=0.036) were significantly associated with faculty development activities. The barriers to faculty training were identified as: lack of incentives 20 (54%), lack of faculty interest 15 (40%), and dearth of trained facilitators 15 (40%). Conclusion: Majority of the medical institutes were involved in faculty development activities imparting training regarding communication and teaching skills. Presence of DME in the college, the respondent’s designation, and the provincial location of the college positively influenced faculty development activities. Lack of incentives, lack of faculty interest and a shortage of trained faculty were identified as barriers. Keywords: Medical College, faculty development, medical education